2022
DOI: 10.1111/soc4.13013
|View full text |Cite
|
Sign up to set email alerts
|

Further resource multiplication at more advanced ages? Interactions between education, parental socioeconomic status, and age in their impacts upon health

Abstract: While scholarship has shown that socioeconomic status creates fine-grained gradients in health, there is debate regarding whether having higher amounts of one socioeconomic resource amplifies (resource multiplication) or reduces (resource substitution) the health benefits of one's other socioeconomic resources. A further question is whether these processes are accentuated or diminished at more advanced ages. Using the 2016 and 2018 waves of the United States General Social Survey (N = 2995) and logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Our additional life-course analyses (Figure 4S) suggest that the mixed findings in previous studies may be partly attributed to differing age distributions in the study samples. Based on samples of adult respondents age 20/25 or older, Bauldry's (2014), Settels' (2022), and Veenstra and Vanzella-Yang's (2022 reported that a college degree was more beneficial for people from advantaged backgrounds. In contrast, Ross and Mirowsky (2011), Schaan (2014), andVable et al (2018) used data of age 60 or older respondents and found evidence supporting the recourse substitution hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our additional life-course analyses (Figure 4S) suggest that the mixed findings in previous studies may be partly attributed to differing age distributions in the study samples. Based on samples of adult respondents age 20/25 or older, Bauldry's (2014), Settels' (2022), and Veenstra and Vanzella-Yang's (2022 reported that a college degree was more beneficial for people from advantaged backgrounds. In contrast, Ross and Mirowsky (2011), Schaan (2014), andVable et al (2018) used data of age 60 or older respondents and found evidence supporting the recourse substitution hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ross and Mirowsky (2011), Schaan (2014) and Vable et al (2018) found that higher education provided more health benefits for those from a disadvantaged background. In contrast, Bauldry (2014), Settels (2022), andVeenstra andVanzella-Yang (2022) suggested that college education is more beneficial for the advantaged. Such mixed findings may be attributed to various sources including different methodological approaches, age samples, and/or health outcomes.…”
Section: For Whom Education Conveys Health Benefits?mentioning
confidence: 97%